Information behavior of undergraduates to preventive measures of corona virus: A post COVID experience - Omotunde, Oluwatobi I.; Oluwaseun, J. Amusan; Ajie, I. Abigail (Kashere Journal of Education, 2023)
This study was conducted with the primarily purpose of evaluating the information awareness, seeking behavior and use of preventive measures of corona virus. The survey research design of the analytical type and a purposive sampling was adopted for the study. The total sample size for this study was five hundred and thirty-eight (538). The instrument for data collection was a questionnaire. A total of 443 (92.7%) copies of questionnaire were returned and found usable. Data collected were analyzed using descriptive and multiple regression statistical tools. The study revealed that respondents were aware that omicron variant of corona virus is a new type of virus. However, majority agreed that the type of genetic materials in corona virus is DNA which contradicts proven studies and research. Findings on information needs of respondents revealed that majority need information on causes, symptoms, test procedures and transmission level of corona virus among others. The result on the sources by which the undergraduates get their information on corona virus revealed that the internet was the major sources of information while library was the least sources of accessing information. Furthermore, findings on the pattern of the use of preventive measures of corona virus information revealed undergraduates utilized the information on corona virus majorly for symptom identification; patient isolation/quarantine procedure and treatment procedure. The result on the regression analysis revealed a significant effect of information sources on attitude to use preventive measures of corona virus. Finally, the result revealed information awareness, needs and use have a significant influence on attitude of undergraduates to preventive measures of the virus. It was concluded that the library was the less consulted source of information related to the corona virus information on health needs. Hence, library should do more in providing accurate and credible health related information to its respective users.